Kuat Tarik Beton Geopolimer Optimum Pada Variasi Perbandingan Bahan Penyusun (20:80 S/D 40:60) Dan Pada Variasi Waktu Pencampuran (5 S/D 15 Menit) - IMRON ALFIDIANDRA, MEY, Ir. Suhendro Trinugroho, M.T (2017)
Concrete is composed of coarse aggregate, fine aggregate, water, and binders such as cement and can also be replaced with flay ash mixed with alkaline activator material so as to form a mixture of material which has properties such as cement. The present study aims to determine the optimum time of geopolymer concrete mixing with a variety of materials were 20%:80%, 25%:75%, 30%:70%, 35%:65%, 40%:60% and on the variation of mixing time 5, 7.5, 10, 12.5, 15 minutes. Mix design refers to earlier research. Number of test objects on each of 3 pieces each variation Award, bringing the total overall test specimens were 75 pieces. The test object is a cylinder with a diameter of 15cm and height 30cm. The results show that geopolymer concrete has the optimum mixing time at 7.5menit. Data for tensile strength test results on the geopolymer concrete sides variaasi 20%:80% ratio of constituent materials and on the variation of mixing time 5mn is 4.044 MPa, 7.5menit is 5.007 MPa, 10min is 4.667 MPa, 12.5 menit is 3.719 MPa, 15 min was 2.993 MPa. At 25%:75% constituent material ratio variation and variation 5 mn mixing time is 4.770 MPa, 7.5menit is 6.622 MPa, 10min is 5.763 MPa, 12.5menit is 4,533 MPa, 15 min was 3,985 MPa. At 30%:70% constituent material ratio variation and variation 5mn mixing time is5.319 MPa, 7.5menit is 7.822 MPa, 10 min is 6.148 MPa, 12.5menit is 4.785 MPa, 15 min was 4.430 MPa. At 35%:65% constituent material ratio variation and variation 5mn mixing time is 4.563 MPa, 7.5menit is 5.926 MPa, 10min is 5.363 MPa, 12.5menit is 4.237 MPa, 15 min was 3.867 MPa. At 40%:60% constituent material ratio variation and variation 5mn mixing time is 4.059 MPa, 7.5menit is 5.526 Mpa, 10min is 4.948 MPa, 12.5menit is 3.985 MPa, 15 min was 3.244 MPa. It can be concluded that the geopolymer concrete mixing time most optimum is7.5 minutes.